Spin Roll Board as Media for Developing the Introduction Pancasila Principles in Elementary School - Fadilah, Nila; Faizah, Maryam (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Metro, 2025)
Pancasila education is very important subject to learn for an early age. Students' knowledge and understanding of the symbols and symbols of Pancasila are still quite low. One of them is influenced by the use of media to arouse students' enthusiasm and interest. So there needs to be innovation in media development, namely developing spin roll board media. The objectives of this research and development are: 1) explain the procedure for developing spin roll board media, 2) determine the attractiveness of spin roll board media. The research used a research and development method adapting the Borg & Gall model. Data collection techniques were used through interviews, observations, and questionnaires. The subjects in this study were 24 students of class 2B at Islamic Elementary School Bani Hasyim Singosari. The results of the material expert validation assessment obtained a percentage of 94%, 96% from media experts, 88% from learning practitioners, and the percentage of attractiveness from students was 91%. Keywords: Media Development, Spin Roll Board Media, Pancasila Principles, Elementary School